The presence of TNF-α and TNFR1 in aseptic root resorption. A preliminary study - Curl Linda; Sampson Wayne (Australasian Orthodontic Journal, 2011)
Background: It is hypothesised that osteoprotegerin (OPG), as an osteoclast antagonist, may offer molecular control over the process of orthodontic root resorption. Previous work investigating OPG in a rat periodontal ligament (PDL) ankylosis model found no inhibitory effect on osteoclasts and odontoclasts when given at a recommended dosage of 2.5 mg/kg. It was considered that traumatically-induced PDL inflammation produces mediators and cytokines with the ability to stimulate clast cell differentiation and counter the effects of OPG.